2018
DOI: 10.1038/s41419-018-0496-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA H19 contributes to apoptosis of hippocampal neurons by inhibiting let-7b in a rat model of temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is one of the most common types of intractable epilepsy, characterized by hippocampal neuron damage and hippocampal sclerosis. Long noncoding RNAs (lncRNAs) have been increasingly recognized as posttranscriptional regulators. However, their expression levels and functions in TLE remain largely unknown. In the present study, TLE rat model is used to explore the expression profiles of lncRNAs in the hippocampus of epileptic rats using microarray analysis. Our results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 48 publications
10
67
0
Order By: Relevance
“…To our knowledge, the regulation of apoptotic genes is cell-type dependent. For instance, previous studies demonstrated that the lncRNA H19 inhibited MC apoptosis [51], but promoted apoptosis in cardiomyocytes and hippocampal neurons [52,53]. Hence, given the cell-type speci city of Dex induced responses, the roles and underlying mechanisms of the genes identi ed in the present study need further elucidation.…”
Section: Discussionmentioning
confidence: 81%
“…To our knowledge, the regulation of apoptotic genes is cell-type dependent. For instance, previous studies demonstrated that the lncRNA H19 inhibited MC apoptosis [51], but promoted apoptosis in cardiomyocytes and hippocampal neurons [52,53]. Hence, given the cell-type speci city of Dex induced responses, the roles and underlying mechanisms of the genes identi ed in the present study need further elucidation.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, LncRNA UCA1, which was downregulated in the epileptiform hippocampal neurons and rat of temporal lobe epilepsy, could obstruct seizure-induced brain injury by modulating miR-495 expression [25]. LncRNA H19 was upregulated during the progression of temporal lobe epilepsy and H19 overexpression provoked SE-induced neuronal apoptosis through sponging let-7b [26]. Based on our finding that overexpression of NEAT1 promoted the neuronal apoptosis, we further studied the functional target of NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lncRNAs have been reported to be associated with neuron apoptosis. As the selected examples, lncRNA MALAT1 [22] and lncRNA H19 [23] contributed to the apoptosis of hippocampal neurons. The present work illustrated that silence of MEG3 prevented hypoxia-induced cell viability loss and apoptosis.…”
Section: Discussionmentioning
confidence: 99%